AUTOMATED THERMOGRAMM CALCULATION OF SAUSAGE COOKING BASED ON COMPUTER MODELS - A.B. LISITSYN; A.M. CHERNUKHA; A.V. BORODIN (Advanced Engineering Research)
Method is described to calculate thermogramms for sausage cooking process. With automated process's parameters correction. Examples of thermoramms describing process first and finish stages for sausages in natural and artificial casings are given.